The road to recovery: Understanding and managing anterior cruciate ligament injuries in athletes - Dias, Heike Felipe Rangel; Dias, Hiann Pedro Rangel; Covolan, Marina Romi Zanatta; Freitas, Diego Macêdo de; Guimarães, Ana Carolina Campos Moraes; Cunha , Nagela Daiane Vieira da; Siqueira , Maria Eduarda Castro Ferreira de; Rangel , Luis Felipe Scampini Siqueira; Ribeiro, Felipe Silva; Tomaz, Heloisa Brandão Muniz (Seven Editora, 2023)
Introduction: Anterior Cruciate Ligament (ACL) injuries are common among athletes participating in high-demand sports. The ACL is an essential ligament in the knee that provides stability against unwanted movements. The incidence of ACL injuries in the United States is significant, becoming a concern for athletes and sports medicine professionals. This text provides an overview of ACL injuries, including their anatomy, function, risk factors, prevention strategies, and effective rehabilitation techniques. ACL rupture can impact athletic performance and require extensive rehabilitation. Methodology: A literature review was conducted from 2010 to 2022 using the databases PubMed, Scielo, and Medline to provide an updated overview of the relationship between Anterior Cruciate Ligament (ACL) injuries and athletes. Twenty-six articles addressing the clinical, anatomical, pathological, and treatment aspects of ACL injuries in athletes were selected. These articles were published in English, Spanish, or Portuguese. The methodological quality of the articles was evaluated, and the data were qualitatively analyzed, grouping the results by similarity. The data synthesis was presented descriptively, highlighting key information about the clinical, anatomical, pathological, and treatment aspects of ACL injuries in athletes. Discussion: This work discusses risk factors, prevention, rehabilitation, surgical treatment, psychological impact, long-term consequences, recent research, and specific considerations for female athletes related to Anterior Cruciate Ligament (ACL) injuries. Risk factors for ACL injuries include increased general joint laxity, increased anterior-posterior knee joint laxity, female sex, previous ACL reconstruction, and familial predisposition to ACL injury. The incidence of ACL injuries varies among different sports and sexes. Injury rates are higher in sports such as soccer, basketball, and baseball/softball. Injury prevention strategies are also discussed. Conclusion: Anterior Cruciate Ligament (ACL) injuries are a significant concern for athletes and sports medicine professionals. A comprehensive approach involving prevention, rehabilitation, and safe return to sport is necessary to reduce the risk of ACL injuries in athletes and prevent long-term consequences. Adequate training techniques, injury prevention programs, and effective rehabilitation approaches play a crucial role in minimizing the risk of ACL injuries in athletes. Additionally, physiotherapists play a vital role in the prevention and rehabilitation of these injuries, and it is essential for them to stay updated with the latest research to provide the most effective care to affected athletes. DOI:https://doi.org/10.56238/globalhealthprespesc-021